Variability of Multiangle Isometric Force-Time Characteristics in Trained Men. Issue 1 (January 2022) - Oranchuk, Dustin J.; Storey, Adam G.; Nelson, André R.; Neville, Jonathon G.; Cronin, John B.
Abstract : Abstract: Oranchuk, DJ, Storey, AG, Nelson, AR, Neville, JG, and Cronin, JB. Variability of multiangle isometric force-time characteristics in trained men. J Strength Cond Res 36(1): 284–288, 2022—Measurements of isometric force, rate of force development (RFD), and impulse are widely reported. However, little is known about the variability and reliability of these measurements at multiple angles, over repeated testing occasions in a homogenous, resistance-trained population. Thus, understanding the intersession variability of multiangle isometric force-time characteristics provides the purpose of this article. Three sessions of isometric knee extensions at 40°, 70°, and 100° of flexion were performed by 26 subjects across 51 limbs. All assessments were repeated on 3 occasions separated by 5–8 days. Variability was qualified by doubling the typical error of measurement (TEM), with thresholds of 0.2–0.6 (small), 0.6–1.2 (moderate), 1.2–2.0 (large), 2.0–4.0 (very large), and >4.0 (extremely large). In addition, variability was deemed large when the intraclass correlation coefficient (ICC) was <0.67 and coefficient of variation (CV) >10%; moderate when ICC >0.67 or CV <10% (but not both); and small when both ICC >0.67 and CV <10%. Small to moderate between-session variability (ICC = 0.68–0.95, CV = 5.2–18.7%, TEM = 0.24–0.49) was associated with isometric peak force, regardless of angle. Moderate to large variability was seen in early-stage (0–50 ms) RFD and impulse (ICC = 0.60–0.80, CV = 22.4–63.1%, TEM = 0.62–0.74). Impulse and RFD at 0–100 ms, 0–200 ms, and 100–200 ms were moderately variable (ICC = 0.71–0.89, CV = 11.8–42.1%, TEM = 0.38–0.60) at all joint angles. Isometric peak force and late-stage isometric RFD and impulse measurements were found to have low intersession variability regardless of joint angle. However, practitioners need to exercise caution when making inferences about early-stage RFD and impulse measures due to moderate-large variability.